METODE SYARAH FATH AL-BARI (Studi Syarah Hadis pada bab Halawah al-Iman) - Aan Supian (Universitas Islam Negeri Fatmawati Sukarno, 2017)
This article aims to find out the methods, approaches and techniques of interpretation of Ibn Hajar’s syarah in Fath al-Bari in understanding the hadith about “halawah al-iman.” From the results of the study shows that : First, Hadiths in chapter “halawah al-iman” contained in Fath al-Bari, is described by the tahlili method; Second, there are at least two approaches used, namely language approach (linguistic) and theological-normative approach; Thirdly, the Interpretation Technique used by Ibn Hajar in prescribing the hadith about halawah al-iman “is a technique of textual and intertextual interpretation